The prevalence of urinary tract infections (UTIs) in the pediatric hospital of Benghazi city, Libya. - Bozakouk, Ismaeel; Abdalla, Ibrahim; Al Orifya, Khawla; Bumediana, Mohamad; Bleibloa, Farag (Libyan Journal of Science &Technology, 2022)
Urinary tract infections (UTIs) are a frequent clinical problem and may have adverse clinical consequences especially for infants and young children. There have been no studies conducted to determine the incidence rate of UTIs among children in Benghazi and the guidelines for the laboratory diagnosis and antimicrobial susceptibility testing remained largely unmanaged. Accordingly, we investigated the prevalence of pediatric UTIs during the first six months of the year 2015 in the pediatric hospital of Benghazi city. About 2100 urine samples were collected from patients presented with clinical signs of UTIs. In both hospitalized patients admitted to different hospital units and from the outpatient department (OPD), the overall bacterial UTIs rate was 15.43% (324 UTI-positive samples). In OPD, the rate of UTIs in boys was 61.83% compared to 45.33% in girls. However, UTIs were more frequent in girls than boys as indicated from samples received from the other hospital internal units. The most common cause of UTIs was Escherichia coli (64.32%). Other responsible agents have included Klebseilla, Proteus, Enterobacter, Pseudomonas, Aeromonas and Streptococcus. The rate of resistance to amoxicillin and norfloxacin was about 40%. Similarly, the other antibacterial drugs routinely used for UTI susceptibility testing revealed less than 30% resistance. Therefore, important factors such as incidence rate of UTIs, standard laboratory diagnosis, and antimicrobial susceptibility testing require a special consideration in children for optimal UTIs treatment.